2015
DOI: 10.1051/0004-6361/201423612
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional AGN-driven turbulence inhibits star formation in the 3C 326N radio galaxy

Abstract: We detect bright [Cii]λ158 μm line emission from the radio galaxy 3C 326N at z = 0.09, which shows no sign of ongoing or recent star formation (SFR < 0.07 M yr −1 ) despite having strong H 2 line emission and a substantial amount of molecular gas (2 × 10 9 M , inferred from the modeling of the far-infrared (FIR) dust emission and the CO(1−0) line emission). The [Cii] line is twice as strong as the 0−0S(1) 17 μm H 2 line, and both lines are much in excess of what is expected from UV heating. We combine infrare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
58
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 115 publications
10
58
0
Order By: Relevance
“…NGC 1266 (Alatalo et al 2015). However, the injection of large amounts of energy in the gas disk may have a similar effect as increasing the turbulence of the gas, a process that is also thought to inhibit star formation (see the case of 3C 326, Guillard et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…NGC 1266 (Alatalo et al 2015). However, the injection of large amounts of energy in the gas disk may have a similar effect as increasing the turbulence of the gas, a process that is also thought to inhibit star formation (see the case of 3C 326, Guillard et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Far-IR molecular observations can provide key and unique insight into the outflow phenomenon: (i) the strength and optical depth of the far-IR continuum generates P-Cygni line profiles in some lines, unambiguously indicating the presence of outflowing gas, discarding other alternatives such as high turbulence or non-circular rotation motions (e.g., Guillard et al 2015;Díaz-Santos et al 2016); (ii) blueshifted absorption can be traced to low velocities, probing low-velocity outflows that may be missed from pure emission lines due to confusion with the line core; (iii) despite the relatively poor spatial resolution of far-IR telescopes, multi-transition observations including high-lying transitions, provide a robust means to quantify the main outflow parameters (mass outflow rate, momentum flux, etc).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interferometric molecular gas observations have shown that the star formation within some quenched objects is suppressed, with inefficiencies of factors of 20-70 (Aalto et al 2016;Alatalo et al 2015aAlatalo et al , 2015cGuillard et al 2015;Lanz et al 2016;Salomé et al 2016), leading to the possibility that star-formationsuppressed molecular reservoirs are a common part of galaxy transformation. However,a larger sample of galaxies must be studied to determine whether this occurs only in rare and energetic objects.…”
Section: Introductionmentioning
confidence: 99%